2014
DOI: 10.1080/15583724.2013.860987
|View full text |Cite
|
Sign up to set email alerts
|

Historical Review of Die Drool Phenomenon in Plastics Extrusion

Abstract: Die drool phenomenon is defined as unwanted spontaneous accumulation of extruded plastics on die exit face(s) of extrusion die during plastics extrusion process. Such accumulated material builds up on die exit face(s) and frequently or continually sticks onto the extruded product and by this way reduces the quality of the product. When the die drool appears, the extrusion process must be shut down and the die exit face(s) must be manually cleaned, which is time consuming as well as money consuming.Die drool ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
(79 reference statements)
0
14
0
1
Order By: Relevance
“…instabilities, see Figure . Comprehensive reviews on the history and developments in this subject can be found in the works of Denn, Larson, Prokunin and Leonov, among others . The melt flow instabilities of polymer melts can be qualitatively categorized into at least two basic categories, which are surface and volume distortions.…”
Section: Introductionmentioning
confidence: 99%
“…instabilities, see Figure . Comprehensive reviews on the history and developments in this subject can be found in the works of Denn, Larson, Prokunin and Leonov, among others . The melt flow instabilities of polymer melts can be qualitatively categorized into at least two basic categories, which are surface and volume distortions.…”
Section: Introductionmentioning
confidence: 99%
“…This cohesive slip layer (drool layer) will emerge from the die and collect on the exterior of the die, forming the die drool. This theory, similar to the fractionation theory, is not exclusive of the adhesive failure mechanism (wall slip) [4]. The fractionation of the resulting die drool has been proposed to the result of thermal degradation, caused by slip heating at the cohesive slip layer.…”
Section: Stress-induced Cohesive Chain Disentanglement (Slip) Theorymentioning
confidence: 86%
“…Die drool has been attributed to external mechanical forces and internal rheology. External die drool generates small flakes or powder in a very short time frame (seconds-minutes), whereas the internal die drool accumulates in compact shapes over a longer time frame (tens of minutes to hours) [4]. Mechanically, external die drool has been attributed to negative (suction) pressure that occurs in the die exit edges (see Figure 1) [4].…”
Section: (I) Die Droolmentioning
confidence: 99%
See 1 more Smart Citation
“…The worm melt fracture could be related to die build‐up (or die drool) phenomena. The die build‐up is the accumulation of polymeric material at the external die surface adjacent to the polymer exiting encountered during many extrusion processes . If portions of the die build‐up intermittently break free from the die lip and attach to the surface of extrudates, it could appear as the worm melt fracture defects.…”
Section: Discussionmentioning
confidence: 99%